Liquid modernity - Bauman, Zygmunt (Polity Press, 2000)
Bauman examines how we have moved away from a 'heavy' and 'solid', hardware-focused modernity to a 'light' and 'liquid', software-based modernity. This passage, he argues, has brought profound change to all aspects of the human condition. The new remoteness and un-reachability of global systemic structure coupled with the unstructured and under-defined, fluid state of the immediate setting of life-politics and human togetherness, call for the rethinking of the concepts and cognitive frames used to narrate human individual experience and their joint history. This book is dedicated to this task. Bauman selects five of the basic concepts which have served to make sense of shared human life - emancipation, individuality, time/space, work and community - and traces their successive incarnations and changes of meaning. Liquid Modernity concludes the analysis undertaken in Bauman's two previous books Globalization: The Human Consequences and In Search of Politics. Together these volumes form a brilliant analysis of the changing conditions of social and political life by one of the most original thinkers writing today.